2012
DOI: 10.1590/s1413-78522012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Desordens musculoesqueléticas em violinistas e violistas profissionais: revisão sistemática

Abstract: Due to the high physical and psychological demands of their work, musicians have a high risk of developing a range of health problems. The main causes of musculoskeletal disorders seen in instrumentalists are overuse, nerve compression and focal dystonia. The aim of this paper is to identify the musculoskeletal disorders that most frequently affect professional violinists and violists. 50 articles were read, of which 24 were used. The PEDro scale was used to determine the quality of the articles. The definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…However, little is known about the fitness levels or indeed the physical characteristics required of musicians to meet these physical demands. Conversely, the existing evidence reveals a high incidence of playing-related musculoskeletal disorders (PRMDs) (Joubrel et al, 2001;Wu, 2007;Brusky, 2010;Ackermann et al, 2012;Moraes and Antunes, 2012;Kok et al, 2013) and pain in the upper body (Engquist et al, 2004;Cruder et al, 2017), as well as pressure to perform and performance anxiety among musicians from early ages (Wesner et al, 1990;van Kemenade et al, 1995;Kenny et al, 2004;Kenny and Ackermann, 2015;Gembris et al, 2018). Research has identified numerous risk factors associated with reported PMRDs and pain, such as playing posture (Nyman et al, 2007;Cruder et al, 2017), hypermobile joints (Dawson, 2002), extended time playing instruments in constrained working conditions (Leaver et al, 2011), and performance anxiety (Kenny and Ackermann, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the fitness levels or indeed the physical characteristics required of musicians to meet these physical demands. Conversely, the existing evidence reveals a high incidence of playing-related musculoskeletal disorders (PRMDs) (Joubrel et al, 2001;Wu, 2007;Brusky, 2010;Ackermann et al, 2012;Moraes and Antunes, 2012;Kok et al, 2013) and pain in the upper body (Engquist et al, 2004;Cruder et al, 2017), as well as pressure to perform and performance anxiety among musicians from early ages (Wesner et al, 1990;van Kemenade et al, 1995;Kenny et al, 2004;Kenny and Ackermann, 2015;Gembris et al, 2018). Research has identified numerous risk factors associated with reported PMRDs and pain, such as playing posture (Nyman et al, 2007;Cruder et al, 2017), hypermobile joints (Dawson, 2002), extended time playing instruments in constrained working conditions (Leaver et al, 2011), and performance anxiety (Kenny and Ackermann, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The review reported a prevalence ranging between 26 and 93%. Further systematic reviews added only limited information, as they did not use predefined review protocols or used a narrow search strategy (Wu 2007;Moraes and Antunes 2012). Furthermore, previous reviews did not focus on the methodological quality of the included studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the prevalence of PRMDs in musicians playing a wide variety of instruments have now been conducted in many European countries, the USA, Brazil and Asia. Prevalence ranges between 26 and 93% (Zaza, 1998 ; Bragge et al, 2006 ; Ranelli et al, 2008 ; Leaver et al, 2011 ; Paarup et al, 2011 ; de Souza Moraes and Antunes, 2012 ; Ackermann et al, 2014 ; Arnason et al, 2014 ; Silva et al, 2015 ; Steinmetz et al, 2015 ; Kok et al, 2016 ; Lonsdale and Kuan Boon, 2016 ; Ciurana Moñino et al, 2017 ; Stanek et al, 2017 ). Kok et al ( 2013 ) suggest that music students might experience musculoskeletal symptoms considerably more often than medical students, especially in the upper body and upper extremity.…”
Section: Introductionmentioning
confidence: 99%